(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Lichens of 75 species from 39 genera, 21 familia, 7 orders are found in the Black forest (Znamenivskiy district, Kirovograds`ka oblast). Among them, Arthonia mediella Nyl., Biatora epixanthoides (Nyl.) Diederich, Bacidina circumspecta (Norrlin & Nyl.) Malme, Cladonia glauca Flоrke та Strangospora ochrophora (Nyl.) R. Anderson are new species for plain part of Ukraine. Epiphytic ecological group prevails here (63 species, 82,5%). The lichens predominantly grow on bark of deciduous trees Quercus (42 species), Fraxinus (35 species) and Acer (30 species).